Angiotensin II and aldosterone in retinal vasculopathy and inflammation. (October 2019) - Wilkinson-Berka, Jennifer L.; Suphapimol, Varaporn; Jerome, Jack R.; Deliyanti, Devy; Allingham, Michael J.
Abstract: Angiotensin II and aldosterone are the main effectors of the renin-angiotensin aldosterone system (RAAS) and have a central role in hypertension as well as cardiovascular and renal disease. The localization of RAAS components within the retina has led to studies investigating the roles of angiotensin II, aldosterone and the counter regulatory arm of the pathway in vision-threatening retinopathies. This review will provide a brief overview of RAAS components as well as the vascular pathology that develops in the retinal diseases, retinopathy of prematurity, diabetic retinopathy and neovascular age-related macular degeneration. The review will discuss pre-clinical and clinical evidence that modulation of the RAAS alters the development of vasculopathy and inflammation in the aforementioned retinopathies, as well as the emerging role of aldosterone and the mineralocorticoid receptor in central serous chorioretinopathy. Highlights: A local renin-angiotensin aldosterone system exists within the retina. Angiotensin II and aldosterone promote vascular pathology and inflammation in the retina. Blockade of renin, the AT1R and ACE reduce retinal vasculopathy and inflammation. Blockade of aldosterone/MRreduce retinal edema and vasculopathy.